Biomagnetic characterization of air pollution particulates in Lahore, Pakistan - Sheikh, HA; Maher, BA; Karloukovski, V; Lampronti, GI; Harrison, RJ (American Geophysical Union, 2022)
We report the characterization of anthropogenic magnetic particulate matter (MPM) collected on leaves from roadside Callistemon (bottlebrush) trees from Lahore, Pakistan, and on known sources of traffic-related particulates to assess the potential of first-order reversal curve (FORC) diagrams to discriminate between different sources of anthropogenic magnetic particles. Magnetic measurements on leaves indicate the presence of surface-oxidized magnetite spanning the superparamagnetic (<30 nm) to single domain (∼30–70 nm) to vortex size range (∼70–700 nm). Fe-bearing particles are present both as discrete particles on the surface of larger mineral dust or carbonaceous particles and embedded within them, such that their aerodynamic sizes may be decoupled from their magnetic grain sizes. FORC diagrams of brake-pad residue specimens show a distinct combination of narrow central ridge, extending from 0 to 200 mT, and a low-coercivity, vertically spread signal, attributed to vortex and multi-vortex behavior of metallic Fe. This is in agreement with scanning electron microscopy results that show the presence of metallic as well as oxidized Fe. Exhaust-pipe residue samples display a more conventional “magnetite-like” signal comprising a lower coercivity central ridge (0–80 mT) and a tri-lobate signal attributed to vortex state and/or magnetostatic interactions. The FORC signatures of leaf samples combine aspects of both exhaust residue and brake-pad endmembers, suggesting that FORC fingerprints have the potential to identify and quantify the relative contributions from exhaust and non-exhaust (brake-wear) emissions. Such measurements may provide a cost-effective way to monitor the changing contribution; of future particulate emissions as the vehicle fleet is electrified over the coming years.